A perspective on the current management of advanced colorectal cancer. (November 2013) - Casagrande, Mariaelena; Cremolini, Chiara; Loupakis, Fotios; Aprile, Giuseppe
Although the median survival of patients with advanced disease has progressively increased, colorectal cancer remains a major worldwide health problem, with approximately 1 million new cases and 500, 000 deaths every year. At the 2013 World Congress on Gastrointestinal Cancers, investigators have recently dealt with many clinically relevant questions, such as the preferred biologic drug to be used upfront in patients with KRAS wild-type colorectal tumors, the optimal treatment intensity, the most suitable maintenance strategy, the need for deeper molecular information when using EGFR inhibitors and the use of antiangiogenic drugs in the elderly. Briefly summarizing all the news coming from this moving landscape, this article focuses on the results of the major randomized Phase III trials presented at the meeting.